Accuracy and reproducibility of turbidity measurements in urban waste water - Ruban, G.; Bertrand-Krajewski, J.L.; Chebbo, G.; Gromaire, M.C.; Joannis, C. (2nd SHF Congress on Microfuids, 2004)
Measuring the turbidity of urban sewage is interesting because in raw waste water, pollutants are mainly particulates and/or bound to particulates. Moreover it is a real time and continuous measurement. This paper deals with knowledge elements and methods for the determination of the components of the uncertainty on turbidity measurement on water samples (principle of measurement, calibration, drift,...). These methods contribute to the use of this measurement technique by operators of urban drainage systems. They were applied for comparing experimental results obtained with various devices and various calibration and sampling strategies. The level of overall short term accuracy reached for turbidity measurement in urban waste water is satisfactory, provided that the non-linearity of some devices to corrected if needed.